The Use of the Quizizz Application for Osing Language Subjects in Class V at Madrasah Ibtidaiyah Negeri 1 Banyuwangi - Rusdi, Rusdi; Rizal, Fauzi; Permatasari, Risa Ayu (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
MIN 1 Banyuwangi implements Osing language learning as local content learning. Osing language is a regional language used to communicate in everyday life by the people of Banyuwangi, Osing language learning is done every 2 weeks on Fridays using the Quizizz application. The use of this application is expected to make it easier for students to learn and understand the Osing language. This research uses a descriptive qualitative approach and a case study type of research. They were determining research subjects using Purposive techniques. Data collection techniques use observation, interviews, and documentation. In analyzing data, researchers use data condensation (Data Condensation), present data (Data Display), and draw conclusions or verification (Conclusion Drawing and Verification). The validity of the data in this research uses technical triangulation and source triangulation. The results show that: 1) Planning to use the Quizzizz application Osing language learning carried out by teachers by determining the syllabus and lesson plans for one semester, as well as preparing the Quizizz application; 2) Implementation of the use of the Quizzizz Osing language learning application includes teachers preparing questions on the Quizizz application; 3) use of the Quizizz application as an alternative media to improve Osing language learning.